(untitled) - Slovis, Corey M. (Philadelphia, PA., 2000)
This pocket-sized volume is a collection of rules, humorous observations, ideas, advice, and helpful tips about a wide variety of topics facing emergency room physicians and other healthcare professionals in an emergency setting.
Keywords: Emergency medicine,Thuốc khẩn cấp